Uptake mechanism of Hepatitis B Virus into susceptible primary hepatocyte cultures - Kott, Nicole; Justus Liebig University Giessen (My University, 2010)
Hepatitis B virus (HBV) can infect only a few cell types including primary Tupaiahepatocytes (PTH) which were used in this work. The aim of the study was to characterizethe early steps of HBV infection using pharmacological inhibitors and confocal microscopy.The distinction between endocytosis in general and direct fusion with the plasmamembrane was made by using hypertonic sucrose concentrations. The fusion of Sendaivirus (SeV) with the plasma membrane and its infectivity was not affected, whereas theinfection of control viruses known to be taken up via endocytosis, e.g. Semliki Forest virus(SFV) and Simian virus 40 (SV40), was impeded. The HBV infection was inhibited in adose-dependent manner, suggesting an endocytic uptake. The dynamin inhibitor Dynasorecompletely inhibited the entry of SFV (clathrin-mediated endocytosis) and SV40 (caveolinmediatedendocytosis), but had no effect on HBV suggesting a dynamin-independentinternalization. Furthermore, the inhibitor of macropinocytosis EIPA did not impair HBVinfection. HBV was also not able to stimulate the macropinocytic activity of PTH. Alsophagocytosis could be ruled out as an entry mechanism. The actin inhibitors Jasplakinolide(actin-stabilisation) or Cytochalasin D (actin-depolymerisation) resulted in a partialinhibition of the early steps of HBV infection. The intracellular transport of HBV could beconstrained by utilization of Nocodazole, an inhibitor of microtubule-polymerisation. HBVdoes not require an acidic pH within the endosomal compartments for the initiation of aproductive infection cycle and therefore differs from many other viruses that areinternalized via endocytosis (e.g. SFV, which was tested as control virus) and also from therelated hepatitis B virus of the duck. No parallels to the retrograde pathway of SV40 wereobserved, since the HBV infection showed no sensitivity towards inhibitors of specificintracellular transport mechanisms (Brefeldin A), ER protein folding and quality factors(MG-132) and the translocation process to the cytosol (Thapsigargin). Together withprevious data it can be concluded that HBV is internalized via a not yet known, possiblyvirus-induced, endocytic uptake mechanism, which is clathrin-, caveolin-, lipid raft- anddynamin-independent and differs from the process of phagocytosis and macropinocytosis.

Hepatitis B Virus (HBV) kann nur wenige Zelltypen infizieren, u.a. primäre TupaiaHepatozyten (PTH), die hier eingesetzt wurden. Die frühen Schritte der HBV-Infektion sindnoch unbekannt und sollten mithilfe von pharmakologischen Inhibitoren und konfokalerMikroskopie charakterisiert werden. Die Unterscheidung zwischen allen Arten vonEndozytosevorgängen und der direkten Fusion von Virushüllen mit der Plasmamembranerfolgte durch Behandlung mit hyperosmolaren Sucrosekonzentrationen. Die Fusion desSendai Virus (SeV) mit der Plasmamembran und dessen Infektiosität wurden dadurch nichtbeeinflusst, während die Infektion endozytisch aufgenommener Kontrollviren, z.B. desSemliki Forest Virus (SFV) sowie des Simian Virus 40 (SV40), unterbunden werden konnte.Auch die Infektion mit HBV wurde dosis-abhängig inhibiert, was auf eine endozytischeAufnahme schließen lässt. Der Dynamin-Inhibitor Dynasore konnte die Eintrittsprozessevon SFV (Clathrin-vermittelte Endozytose) und SV40 (Caveolin-vermittelte Endozytose)vollständig unterbinden, hatte jedoch keinen Einfluss auf die HBV-Infektion, was auf einenDynamin-unabhängigen Internalisierungsprozess hindeutet. Auch der Inhibitor derMakropinozytose EIPA inhibierte die HBV-Aufnahme nicht. Außerdem stimulierte HBVnicht die Makropinozytose in PTH. Phagozytose konnte als Eintrittsmechanismus ebenfallsausgeschlossen werden. Die Aktin-Inhibitoren Jasplakinolide (Aktin-Stabilisierung) bzw.Cytochalasin D (Aktin-Depolymerisierung) führten zu einer partiellen Inhibition der frühenSchritte der HBV Infektion. Der intrazelluläre Transport von HBV konnte durch Nocodazol,einem Inhibitor der Mikrotubuli-Polymerisation, behindert werden. HBV benötigt für dieInfektion keinen sauren pH innerhalb der endosomalen Kompartimente und unterscheidetsich damit von vielen anderen endozytisch aufgenommenen Viren (u.a. dem KontrollvirusSFV) und auch vom verwandten Hepatitis B Virus der Ente. Ein retrograder Aufnahmewegwie bei SV40 liegt bei HBV nicht vor, da entsprechende Inhibitoren bestimmterintrazellulärer Transportprozesse (Brefeldin A), ER-Proteinfaltungs-und Qualitätsfaktoren(MG-132) sowie des Translokationsprozesses ins Zytosol (Thapsigargin) wirkungslosblieben. Zusammen mit früheren Daten kann postuliert werden, dass HBV über einenbislang unbekannten, möglicherweise vom Virus selbst-induzierten, endozytischenAufnahmemechanismus internalisiert wird, welcher Clathrin-, Caveolin-, lipid raft- undDynamin-unabhängig ist und sich vom Prozess der Phagozytose und Makropinozytoseunterscheidet.
Aufnahmemechanismus des Hepatitis B Virus in suszeptible primäre Hepatozyten Kulturen
Keywords: Hepatitis B Virus; primäre Tupaia Hepatozyten; Endozytose; Hepatitis B Virus; primary Tupaia hepatocyte; endocytosis; ddc:570